Food sovereignty and the agrarian question in South Africa: Class Dynamics and Collective Agency from Below - Bennie, Andrew Govan (University of the Witwatersrand, Johannesburg, 2023)
In South Africa – one of the most unequal countries in the world – patterns of food insecurity, hunger and malnutrition exist in conjunction with a dominant agro-food system that is highly modernised, commercialised and globally integrated, and includes a deeply unequal agrarian structure. Globally, there has been an upsurge in movement organising around the ecological and social impacts of the corporate food system. One of the most prominent political responses has been the food sovereignty movement. The politics of food sovereignty, however, is ultimately grounded and constituted in situated national and local contexts. The research for this thesis therefore sought to understand the nature of civil society organising from below in South Africa in response to the various inequalities of the agro-food system (the ‘food movement’), with which the global discourse and practice of food sovereignty articulates. I therefore argue that there is an emergent ‘food movement’ in South Africa whose character (and limits) reflects its construction through historical and ongoing conjunctural, contingent and contextual relationships between the agrarian and national questions, political struggles under national oppression, and the social, economic and ecological contradictions of national liberation in the post-apartheid order. The thesis is grounded in the conceptual frame of the agrarian question, a critical agrarian political economy approach that has principally been concerned with the relationship between agriculture and capitalism, the class relations within agriculture, and the associated politics arising out of the agrarian question. It is situated in the agrarian debate on food sovereignty, broadly construed as that between ‘agrarian populism’ and ‘agrarian Marxism’. It adopts a materialist analysis that is combined with historical and political specificity, open to the ways in which political agency is an important factor shaping the course of agrarian change. The research adopted a qualitative approach framed by Michael Burawoy’s extended case study method combined with elements of Gillian Hart’s method of relational comparison. Data was gathered primarily through an analysis of secondary and primary literature, extensive interviews, participant observation, and two case studies. To understand the terrain of food organising from below, the thesis examines the historically conjunctural, contingent and contextual processes that both underpinned the formation of the dominant agro-food system and to which that system contributed. It does this by weaving the history of food and hunger to the history of class formation, political resistance and organising, and larger historical developments. This sets the scene for understanding the origins and nature of the contemporary ‘food movement’ in South Africa. A typology shows that the array of organising around food and the agro-food system today falls along a continuum between justice-centred and food-centred conceptions of change in the food system, and that they cohere around lifestyle, organic, food justice and transformative politics. Importantly, these types should be understood through a longer history of varying political responses to national oppression and the evolving agrarian question, and to the continuities, limits and opportunities of national liberation. The thesis also analyses how these relational categories play out in specific local agrarian contexts of working class communities, showing that the form they take in a given context is shaped by the articulation of a number of conditions and factors. This is done through an examination of the political intersections between agriculture and the struggle against proposed mining in Amadiba in the Eastern Cape Province, and efforts by a smallholder farmer association in Limpopo Province to advance a food sovereignty politics through agroecology. I show that material socio-ecological conditions in situated contexts play an important role in shaping the form, potential and limits of agro-food politics, including patterns of differentiation, hegemonic state-society relationships, and fragmentation of subaltern classes. However, I show that the possibilities for transformative agro-food politics are also contingent on articulations between political histories and practices, the role of the state, and the nature of alliances. I conclude with the need to view food sovereignty not only through a structural lens of an endpoint and blueprint for food production and distribution, but also in terms of how its impulses might (or might not) contextually and conjuncturally connect with efforts to build transformative politics that seek non-alienated production and living, distributional justice, and the secure socio-ecological reproduction of life and living labour.
A thesis submitted in partial fulfillment of the requirements for the degree of Degree of Doctor of Philosophy to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023
Keywords: Agrarian question; Food sovereignty; Food movement; Articulation; UCTD; SDG-2: Zero hunger